On the shortcomings of the plea agreement - Milošević, Dragana (Glasnik Advokatske komore Vojvodine, 2021)
The plea agreement is an institute od criminal procedure law that was introduced into the Criminal Procedure Code in 2011. as one of the three agreements that can be concluded by the public prosecutor and the defendant. The autor points out the shortcomings of the agreement in therms of the absence of the prescribed penalty as a condition for concluding an agreement, sentencing without evidence, with an emphasis on mitigating and aggravating circumstances, where at the same time gives suggestions on how to prevent or eliminate problems in practice could occure by applying valid legal solutions. In order to obtain answers to some of the above questions, a research questionnaire was created on the basis of which the autor collected data in a certain court and prosecutor office in order to prove the presented hypotheses. In addition to the documentary analysis, from the methodological aspect, the comparative and historical method, the prediction strategy and the medium-scale method were used for the purpose of the research.